Computer method for the analysis of evoked motor unit potentials: 1. Control subjects and patients with myasthenia gravis. Issue 11 (November 1974) - Ballantyne, John P.; Hansen, Stig
Abstract : An on-line computer method is described for the isolation of single motor unit potentials, evoked by stimulation of the anterior tibial nerve at the ankle, from the compound action potential recorded from surface electrodes over the extensor digitorum brevis muscle. The latencies, durations, amplitudes, and areas of the potentials were measured in a group of control subjects and patients with myasthenia gravis. In myasthenic patients there is a significant reduction in the durations of motor unit potentials and a significant increase in latencies while their amplitudes and areas remain unchanged. The results are consistent with the presence of a `terminal neuropathy' in myasthenia gravis.